An Airboat For Rural Riverine Transportation and Mangrove Marine Environment Applications - Abdullah, M.O; Yek, P.N.Y; Hamdan, S.; Junaidi, E.; Kuek, P. (International journal of recent research and applied studies, 2010)
The present works describe the design and initial performance study of a prototype airboat for riverine transportation, including mangrove habitat applications, with particular reference to Sarawak, East Malaysia. Many local rural riverine transportation and marine habitat studies are limited due to tide-line dependent and the limitation of conventional blade type marine engine. The use of airboat could ply at the local everglades areas and shallow waters; however the conventional airboat having flat bottom hall may at times not suitable in the narrow mangrove habitat which generally has extended roots. In the present study, our boat was custom designed with Shallow-Vee hall shape, employing a 2-stroke engine. Experimental results have shown that the new airboat built has good performance and balancing capability. Subsequent simulation study employing PROLINE software suggest that 2 passengers as the optimum number for the airboat overall performance (optimum performance and stability), coherent with the experimental trials. Compared with conventional air boats, the new boat design is likely to have two added advantages: (1) relative cheap cost and affordable in development, and (2) shallow-Vee shape design is more suitable then the wider flat bottom shape type due to narrow mangrove habitat, where the shallow mangrove trees generally having roots in the water and extended roots on the water surface.